Developing Describe Text Materials By Using Clustering Technique In SMA Gajah Mada Medan - Dari, Windi Wulan; Sumarsih, Sumarsih (Universitas Negeri Medan, 2023)
The objective of this study was to develop descriptive text writing material by using clustering technique to fulfill the needs of tenth grade students at SMA Gajah Mada Medan. This research was conducted using the Research and Development (R&D) Method. The Research and Development process were divided into six stages: gathering information and data, analyzing data, designing material, expert validation, revising material, and finally, the final product. To discover what the students needed, data were gathered by handing out questionnaires to 38 tenth grade students and interviewing the English teacher at SMA Gajah Mada Medan. The study's findings led to the creation of INTRODUCTION descriptive text writing materials in PDF format that focus on the description of a location, particularly tourist attractions. The developed materials may be used as engaging learning tools for students. The product was validated by two experts, and the average score of their validations was 78% for content, 80% for presentation, 75% for language, and 85% for layout. The overall average was 79.5%, which was considered good and recommended for use in English classes, particularly for writing descriptive language at the senior high school level.